2008
DOI: 10.1373/clinchem.2008.103580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemoglobin (Hb) E and HbD Traits on Measurements of Glycated Hb (HbA1c) by 23 Methods

Abstract: Background: Glycohemoglobin (GHB), reported as hemoglobin (Hb) A1c, is a marker of long-term glycemic control in patients with diabetes and is directly related to risk for diabetic complications. HbE and HbD are the second and fourth most common Hb variants worldwide. We investigated the accuracy of HbA1c measurement in the presence of HbE and/or HbD traits. Methods: We evaluated 23 HbA1c methods; 9 were immunoassay methods, 10 were ion-exchange HPLC methods, and 4 were capillary electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 9 publications
5
63
1
3
Order By: Relevance
“…An international consensus committee has recommended that results should be reported worldwide in both SI units (mmol ⁄ mol) and derived NGSP ⁄ DCCT units (%) [38]. Acknowledging the limitations of the ADAG study, the consensus committee decided against the routine HbC [92] HbE [93] HbD [93] Hereditary persistence of HbF [94] Chemical derivatives of haemoglobin Carbamylated haemoglobin (e.g. as a result of uraemia) [95] Acetylated haemoglobin (e.g.…”
Section: Reporting Hba 1c Resultsmentioning
confidence: 99%
“…An international consensus committee has recommended that results should be reported worldwide in both SI units (mmol ⁄ mol) and derived NGSP ⁄ DCCT units (%) [38]. Acknowledging the limitations of the ADAG study, the consensus committee decided against the routine HbC [92] HbE [93] HbD [93] Hereditary persistence of HbF [94] Chemical derivatives of haemoglobin Carbamylated haemoglobin (e.g. as a result of uraemia) [95] Acetylated haemoglobin (e.g.…”
Section: Reporting Hba 1c Resultsmentioning
confidence: 99%
“…Several reports have included analysis of the effects of these hemoglobins on Hb A 1c results (31)(32)(33)(34). The findings are summarized on the NGSP Web site (48 ).…”
Section: Interferences With Hb a 1c Testingmentioning
confidence: 99%
“…Little et al [6] showed that most HPLCs gave artificially low HbA1c results when compared to affinity chromatography. No clinically significant difference was found for HbA1c results measured with immunoassay.…”
Section: Resultsmentioning
confidence: 99%